Establishment of an induced pluripotent stem cell line (FDEENTi001-A) from a patient with pathological myopia - Bai, Xinyue (Stem Cell Res, 2018)
Pathological myopia (PM) is a retinal degenerative disease with an increasing prevalence in Asia. The peripheral blood mononuclear cells (PBMCs) from a patient with PM were successfully reprogrammed to induced pluripotent stem cells (iPSCs) using integration-free method, Sendai viral (SeV) vectors expressing OCT4, SOX2, KLF4 and C-MYC. This line may provide a useful resource for exploring the pathogenesis of PM.